Efficient and environment-friendly chemical polishing solution and preparation method thereof
By using green and environmentally friendly raw materials such as nanometal abrasives and silicon oxide abrasives in the polishing liquid, and combined with appropriate pH adjustment, the existing polishing liquid has solved the problem of material damage and environmental pollution under high pressure, and achieved an efficient and environmentally friendly polishing effect.
Patent Information
- Application Number
- CN202411845993.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-16
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-12-16
AI Technical Summary
The existing polishing liquid requires high operating pressure during processing, resulting in damage to the material surface, and the chemical reagents used pose potential risks to the environment and the human body, and the components are complex, costly and have high pollution.
A chemical polishing liquid consisting of nanometal abrasives, silicon oxide abrasives, oxidants, complexing agents, corrosion inhibitors and surfactants is used, and the pH value of the liquid is adjusted to 7.5-8.5 through a pH adjuster to form an efficient and environmentally friendly polishing liquid.
Under low operating pressure conditions, the alloy surface scratches are significantly reduced, the dispersion and stability of the polishing liquid are improved, the polishing efficiency is enhanced, the environmental pollution is reduced, and the production cost is reduced.
Smart Images

Figure BDA0005189209630000091
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polishing liquid, and in particular to a highly efficient and environmentally friendly chemical polishing liquid and a preparation method thereof. Background Art
[0002] Chemical mechanical polishing, as a widely used surface flattening technology, has become one of the important processes for precision polishing of alloy surfaces in the fields of precision metal parts, electronic components, and semiconductor device manufacturing. Chemical mechanical polishing is a processing method that combines the chemical action of additives in the polishing liquid with the mechanical action of abrasive particles. The polishing liquid is the key to the polishing effect. However, at present, most polishing liquids still use single abrasive particles or traditional abrasive particles as polishing abrasives. However, due to factors such as their own shape, size, and dispersibility, single abrasive particles have a greater impact on the polishing effect, so more chemical reagents are often needed to improve the polishing effect. On the other hand, most polishing liquids currently use chemical reagents such as strong acids, BTA, and potassium nitrate that have potential risks to the environment and human body. The components of the polishing liquid are complex, the cost is high, the pollution is large, and it is necessary to match a higher polishing pressure, which is easy to cause material surface processing damage. Therefore, how to effectively control the interface contact state between the abrasive and the sample under low operating pressure conditions, thereby reducing the scratches on the alloy surface, and at the same time giving the polishing liquid the characteristics of high efficiency and environmental protection, is one of the key issues that need to be solved in the current production of polishing liquids. Summary of the invention
[0003] The purpose of the present invention is to provide a highly efficient and environmentally friendly chemical polishing liquid and a preparation method thereof in order to solve the above-mentioned deficiencies in the prior art.
[0004] The purpose of the present invention is achieved through the following technical scheme: an efficient and environmentally friendly chemical polishing liquid, comprising the following raw materials in weight percentage: 5%-8% nano metal abrasive, 2%-4% silicon oxide abrasive, 2%-10% oxidant, 1%-5% complexing agent, 0.05%-0.5% corrosion inhibitor, 0.01%-0.3% surfactant, and the rest is deionized water; and also includes a pH regulator, and the pH of the chemical polishing liquid is adjusted to 7.5-8.5 by the pH regulator.
[0005] Furthermore, the nano metal abrasive includes at least one of nano cerium oxide, nano aluminum oxide, and nano zinc oxide.
[0006] Furthermore, the nano metal abrasive is composed of nano cerium oxide and nano aluminum oxide in a mass ratio of 1:0.5-0.7.
[0007] Furthermore, the preparation method of the nano cerium oxide includes the following steps: taking cerium nitrate and fully dissolving it in deionized water to obtain a cerium nitrate solution, then adding acetic acid and ethylene glycol solution to the cerium nitrate solution in sequence and stirring evenly, then transferring it to a reactor, reacting at 175-190°C for 2-3h, cooling naturally after the reaction, centrifuging, washing, and drying, and then roasting at 400-500°C for 3-4h to obtain the nano cerium oxide.
[0008] Furthermore, the concentration of the cerium nitrate solution is 0.8-1.2 g / mL. The particle size of the nano-cerium oxide obtained by the above preparation steps is 130-160 nm.
[0009] Furthermore, the nano cerium oxide is cerium oxide doped with rare earth metal ions, and the rare earth metal ions are preferably La, Pr or Sm. Rare earth metal particles are doped into cerium oxide to adjust the oxygen vacancy concentration on the surface of cerium oxide, thereby enhancing its chemical reaction ability with the surface of silicon wafers, that is, it is possible to increase the Ce of cerium oxide abrasives and improve the polishing efficiency of cerium oxide abrasives. In the present invention, the preparation method of cerium oxide doped with rare earth metal ions comprises the following steps: taking cerium nitrate and fully dissolving it in deionized water to obtain a cerium nitrate solution, then adding acetic acid and ethylene glycol solution to the cerium nitrate solution in sequence and stirring evenly, then dropping a rare earth metal nitrate solution therein, then transferring it to a reactor, reacting at 175-190°C for 2-3h, cooling naturally after completion, centrifuging, washing, and drying, and then roasting at 400-500°C for 3-4h to obtain the nano cerium oxide doped with rare earth metal particles.
[0010] Furthermore, the nano-alumina is a nano-alumina having a silicon oxide coating layer on its surface, and its preparation method comprises the following steps: taking the nano-alumina into a reactor, adding ethanol and deionized water in sequence, ultrasonically mixing, then adding hexadecyltrimethylammonium bromide and sodium hydroxide thereto and mixing evenly, then adding TEOS dropwise, stirring and reacting at room temperature for 6-12 hours, and after completion, centrifuging, washing, and drying to obtain the nano-alumina having a silicon oxide coating layer on its surface.
[0011] Furthermore, the particle size of the nano-aluminum oxide is 5-20 nm; and the thickness of the silicon oxide coating layer is 9-13 nm.
[0012] In the present invention, by coating the surface of nano-alumina with silicon oxide, the risk of damage to the polishing interface caused by the high hardness of nano-alumina is reduced, the quality of the polishing surface is improved, and the dispersibility and stability of alumina can be significantly improved.
[0013] Furthermore, the particle size of the silicon oxide abrasive is 30-60 nm. In the present invention, the preparation method of the silicon oxide abrasive comprises the following steps: adding an ammonia-ammonium chloride buffer solution to a container filled with deionized water, and stirring it thoroughly to obtain a buffer solution; then adding ethyl orthosilicate dropwise to the buffer solution in small amounts for multiple times, heating the solution to 75-85° C. while stirring, reacting for 12-16 hours to obtain silica sol, and then rotary evaporating the silica sol to obtain the silicon oxide abrasive.
[0014] In the present invention, the silicon oxide abrasive prepared by the above preparation method has uniform particle size, good dispersibility, and is not easy to agglomerate, so that it can be evenly dispersed and has good stability in the polishing liquid system. By combining small-sized silicon oxide abrasives with nano-metal abrasives, the small-sized silicon oxide abrasives are conducive to further reducing the surface roughness and improving the polishing surface quality, so that the chemical polishing liquid is suitable for precision polishing.
[0015] Furthermore, the oxidant is hydrogen peroxide, NaClO, K 2 S 2 O 8 Any one of .
[0016] Furthermore, the complexing agent is at least one of glycine, potassium hydrogen phthalate, and sorbitol. As a preferred embodiment of the present invention, the complexing agent is composed of glycine and potassium hydrogen phthalate in a mass ratio of 1.5-2:1. The present invention uses green and environmentally friendly glycine to complex with metal impurity particles such as copper and iron, and potassium hydrogen phthalate has a strong complexing effect on high-valent metal particles. It can meet the use of various polishing conditions within a wide temperature and pH range, and effectively ensure its polishing effect, reduce the impact on the environment, and reduce the production cost of the polishing liquid.
[0017] Furthermore, the corrosion inhibitor is at least one of 1,2,4-triazole, polyvinyl pyrrolidone, disodium hydrogen phosphate, and sodium benzoate. As a preferred embodiment of the present invention, the corrosion inhibitor is composed of 1,2,4-triazole and polyvinyl pyrrolidone in a mass ratio of 2-3:1. The present invention can have a good sustained release effect on metals by combining 1,2,4-triazole and polyvinyl pyrrolidone, and form a protective film on the surface of the silicon wafer, reduce the direct contact between the abrasive in the polishing liquid and the surface of the silicon wafer, and play a sustained release role. It is also beneficial to the dispersion and stability of the abrasive.
[0018] Furthermore, the surfactant is at least one of octylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, hexadecyl trimethyl ammonium bromide, and sodium dodecyl benzene sulfonate. As a preferred embodiment of the present invention, the surfactant is composed of dodecyl trimethyl ammonium bromide and fatty alcohol polyoxyethylene ether in a mass ratio of 1:1-1.2. The present invention can reduce the interfacial tension between the polishing liquid and the silicon wafer, improve the polishing efficiency and uniformity, and is also conducive to the dispersion of the abrasive and prevents its agglomeration by co-combining dodecyl trimethyl ammonium bromide and fatty alcohol polyoxyethylene ether.
[0019] Furthermore, the pH adjuster is at least one of dihydrogen phosphate-hydrogen phosphate buffer, aminopropanol, polyamine organic base, oxalic acid, and L-malic acid.
[0020] The present invention also provides a method for preparing the above-mentioned efficient and environmentally friendly polishing liquid, comprising the following steps: mixing nano metal abrasives, silicon oxide abrasives and deionized water into a suspension and performing ultrasonic dispersion, then adding an oxidant, a corrosion inhibitor, a complexing agent and a surfactant thereto and stirring evenly, and then adding a pH adjuster to adjust the pH of the solution to 7.5-8.5.
[0021] The beneficial effects of the present invention are as follows: the chemical polishing liquid prepared by the present invention using green and environmentally friendly raw materials has good dispersibility and stability, and at the same time shows a good polishing effect in the fine processing of silicon wafers, and its material removal efficiency is high, and the surface of the polished silicon wafer is smooth and undamaged. The present invention plays an important role in improving the polishing efficiency and surface effect of the polishing liquid by forming abrasives with a precise ratio of nano-cerium oxide, nano-aluminum oxide and silicon oxide. At the same time, by adding such complexing agents, the use conditions and scope of the polishing liquid can be broadened under the premise of ensuring the polishing effect; by adding specific corrosion inhibitors, a good slow release effect can be achieved; and by cooperating with dodecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether, the interfacial tension between the polishing liquid and the silicon wafer can be reduced, and the polishing efficiency and uniformity can be improved. The solution system composed of the above-mentioned complexing agent, corrosion inhibitor and surfactant is more conducive to the dispersion and stability of the abrasive. DETAILED DESCRIPTION
[0022] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with embodiments, and the contents mentioned in the implementation modes are not intended to limit the present invention.
[0023] Example 1
[0024] The present embodiment provides an efficient and environmentally friendly chemical polishing liquid, comprising the following raw materials in weight percentage: 6% nano-metal abrasive, 2% silicon oxide abrasive, 3% oxidant, 1.2% complexing agent, 0..08% corrosion inhibitor, 0.03% surfactant, and the rest is deionized water; it also includes a pH regulator, and the pH of the chemical polishing liquid is adjusted to 7.5 by the pH regulator.
[0025] Furthermore, the nano metal abrasive is composed of nano cerium oxide and nano aluminum oxide in a mass ratio of 1:0.5.
[0026] Furthermore, the preparation method of the nano cerium oxide includes the following steps: taking 1g of cerium nitrate and fully dissolving it in deionized water to obtain a cerium nitrate solution, then adding 1ml of acetic acid and 30ml of ethylene glycol solution to the cerium nitrate solution in sequence and stirring evenly, then transferring it to a reactor, reacting at 180°C for 2.5h, cooling naturally after the reaction, removing the supernatant by centrifugation, repeatedly washing with water and ethanol, drying in a 60°C oven overnight, and calcining at 450°C for 3.5h to obtain the nano cerium oxide.
[0027] Furthermore, the concentration of the cerium nitrate solution is 0.9 g / mL. The average particle size of the nano-cerium oxide obtained by the above preparation steps is 150 nm.
[0028] Furthermore, the nano-alumina is a nano-alumina having a silicon oxide coating layer on the surface, and its preparation method comprises the following steps: taking 1g of nano-alumina into a reactor, adding 80mL of ethanol and 20mL of deionized water in sequence, ultrasonically mixing, then adding 5g of hexadecyltrimethylammonium bromide and sodium hydroxide thereto and mixing evenly, then adding TEOS dropwise, stirring and reacting at room temperature for 6h, and after completion, centrifuging, washing and drying to obtain the nano-alumina having a silicon oxide coating layer on the surface.
[0029] Furthermore, the nano-alumina is spherical, with a particle size of 20 nm; and the thickness of the silicon oxide coating layer is 10 nm.
[0030] Furthermore, the particle size of the silicon oxide abrasive is 30nm. The preparation method of the silicon oxide abrasive comprises the following steps: adding an ammonia-ammonium chloride buffer solution to a container containing deionized water, and stirring thoroughly to obtain a buffer solution with a pH of 10.5; then adding a small amount of ethyl orthosilicate (the mass ratio of deionized water to ethyl orthosilicate is 1.2:1) to the buffer solution, heating to 75°C while stirring, reacting for 12h to obtain silica sol, and then subjecting the silica sol to rotary evaporation at 50°C, and vacuum drying to obtain the silicon oxide abrasive.
[0031] Further, the oxidant is K 2 S 2 O8 .
[0032] Furthermore, the complexing agent is composed of glycine and potassium hydrogen phthalate in a mass ratio of 1.5:1.
[0033] Furthermore, the corrosion inhibitor is composed of 1,2,4-triazole and polyvinyl pyrrolidone in a mass ratio of 2:1.
[0034] Furthermore, the surfactant is composed of dodecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether in a mass ratio of 1:1.05.
[0035] Furthermore, the pH regulator is aminopropanol.
[0036] The preparation method of the efficient and environmentally friendly polishing liquid described in this embodiment includes the following steps: mixing nano metal abrasives, silicon oxide abrasives and deionized water into a suspension and ultrasonically dispersing it, then adding an oxidant, a corrosion inhibitor, a complexing agent and a surfactant thereto and stirring them evenly, and then adding a pH adjuster to adjust the pH of the solution to 7.5.
[0037] Example 2
[0038] The present embodiment provides an efficient and environmentally friendly chemical polishing liquid, comprising the following raw materials in weight percentage: 7% nano-metal abrasive, 3% silicon oxide abrasive, 5% oxidant, 3% complexing agent, 0.2% corrosion inhibitor, 0.15% surfactant, and the rest is deionized water; it also includes a pH regulator, and the pH of the chemical polishing liquid is adjusted to 8.0 by the pH regulator.
[0039] Furthermore, the nano metal abrasive is composed of Pr-doped nano cerium oxide and nano aluminum oxide in a mass ratio of 1:0.6.
[0040] Furthermore, the preparation method of the Pr-doped nano-cerium oxide includes the following steps: taking 1g of cerium nitrate and fully dissolving it in deionized water to obtain a cerium nitrate solution, then adding 1ml of acetic acid and 30ml of ethylene glycol solution to the cerium nitrate solution in sequence and stirring it evenly, then dropping praseodymium nitrate solution therein, and then transferring it to a reactor, reacting at 180°C for 2.5h, cooling naturally after the end, removing the supernatant by centrifugation, repeatedly washing with water and ethanol, drying in an oven at 60°C overnight, and calcining at 450°C for 3.5h to obtain the Pr-doped nano-cerium oxide.
[0041] Furthermore, the concentration of the cerium nitrate solution is 1.0 g / mL, and the concentration of the praseodymium nitrate solution is 0.5 g / mL. The average particle size of the nano cerium oxide obtained by the above preparation steps is 140 nm, and the atomic percentage of Pr doped in the cerium oxide is 2%.
[0042] Furthermore, the nano-alumina is a nano-alumina having a silicon oxide coating layer on the surface, and its preparation method comprises the following steps: taking 1g of nano-alumina into a reactor, adding 80mL of ethanol and 20mL of deionized water in sequence, ultrasonically mixing, then adding 5g of hexadecyltrimethylammonium bromide and sodium hydroxide thereto and mixing evenly, then adding TEOS dropwise, stirring and reacting at room temperature for 10 hours, and after completion, centrifuging, washing, and drying to obtain the nano-alumina having a silicon oxide coating layer on the surface.
[0043] Furthermore, the nano-aluminum oxide is spherical, with a particle size of 10 nm; and the thickness of the silicon oxide coating layer is 11 nm.
[0044] Furthermore, the particle size of the silicon oxide abrasive is 40nm. The preparation method of the silicon oxide abrasive comprises the following steps: adding an ammonia-ammonium chloride buffer solution to a container containing deionized water, and stirring thoroughly to obtain a buffer solution with a pH of 10.5; then adding a small amount of ethyl orthosilicate (the mass ratio of deionized water to ethyl orthosilicate is 1.2:1) to the buffer solution, heating to 80°C while stirring, reacting for 12h to obtain silica sol, and then subjecting the silica sol to rotary evaporation at 50°C, and vacuum drying to obtain the silicon oxide abrasive.
[0045] Furthermore, the oxidant is hydrogen peroxide.
[0046] Furthermore, the complexing agent is composed of glycine and potassium hydrogen phthalate in a mass ratio of 1.5:1.
[0047] Furthermore, the corrosion inhibitor is composed of 1,2,4-triazole and polyvinyl pyrrolidone in a mass ratio of 2.5:1.
[0048] Furthermore, the surfactant is composed of dodecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether in a mass ratio of 1:1.1.
[0049] Furthermore, the pH regulator is potassium dihydrogen phosphate-potassium hydrogen phosphate buffer.
[0050] The method for preparing the efficient and environmentally friendly polishing liquid described in this embodiment includes the following steps: mixing nano metal abrasives, silicon oxide abrasives and deionized water into a suspension and ultrasonically dispersing the suspension, then adding an oxidant, a corrosion inhibitor, a complexing agent and a surfactant thereto and stirring them evenly, and then adding a pH adjuster to adjust the pH of the solution to 8.0.
[0051] Example 3
[0052] The present embodiment provides an efficient and environmentally friendly chemical polishing liquid, comprising the following raw materials in weight percentage: 7% nano-metal abrasive, 3% silicon oxide abrasive, 6% oxidant, 3% complexing agent, 0.3% corrosion inhibitor, 0.2% surfactant, and the rest is deionized water; it also includes a pH regulator, and the pH of the chemical polishing liquid is adjusted to 8.0 by the pH regulator.
[0053] Furthermore, the nano metal abrasive is composed of La-doped nano cerium oxide and nano aluminum oxide in a mass ratio of 1:0.6.
[0054] Furthermore, the preparation method of the La-doped nano-cerium oxide includes the following steps: taking 1g of cerium nitrate and fully dissolving it in deionized water to obtain a cerium nitrate solution, then adding 1ml of acetic acid and 30ml of ethylene glycol solution to the cerium nitrate solution in sequence and stirring evenly, then dropping lanthanum nitrate solution therein, and then transferring it to a reactor, reacting at 180°C for 2.5h, cooling naturally after the end, removing the supernatant by centrifugation, repeatedly washing with water and ethanol, drying in an oven at 60°C overnight, and calcining at 450°C for 4h to obtain the La-doped nano-cerium oxide.
[0055] Furthermore, the concentration of the cerium nitrate solution is 1.0 g / mL, and the concentration of the lanthanum nitrate solution is 0.5 g / mL. The average particle size of the nano cerium oxide obtained by the above preparation steps is 150 nm, and the atomic percentage of La doped in the cerium oxide is 2%.
[0056] Furthermore, the nano-alumina is a nano-alumina having a silicon oxide coating layer on the surface, and its preparation method comprises the following steps: taking 1g of nano-alumina into a reactor, adding 80mL of ethanol and 20mL of deionized water in sequence, ultrasonically mixing, then adding 5g of hexadecyltrimethylammonium bromide and sodium hydroxide thereto and mixing evenly, then adding TEOS dropwise, stirring and reacting at room temperature for 12h, and after completion, centrifuging, washing and drying to obtain the nano-alumina having a silicon oxide coating layer on the surface.
[0057] Furthermore, the particle size of the nano-aluminum oxide is 10 nm; and the thickness of the silicon oxide coating layer is 12 nm.
[0058] Furthermore, the particle size of the silicon oxide abrasive is 40nm. The preparation method of the silicon oxide abrasive comprises the following steps: adding an ammonia-ammonium chloride buffer solution to a container containing deionized water, and stirring thoroughly to obtain a buffer solution with a pH of 10.5; then adding a small amount of ethyl orthosilicate (the mass ratio of deionized water to ethyl orthosilicate is 1.2:1) to the buffer solution, heating to 80°C while stirring, reacting for 12h to obtain silica sol, and then subjecting the silica sol to rotary evaporation at 50°C, and vacuum drying to obtain the silicon oxide abrasive.
[0059] Furthermore, the oxidant is hydrogen peroxide.
[0060] Furthermore, the complexing agent is composed of glycine and potassium hydrogen phthalate in a mass ratio of 2:1.
[0061] Furthermore, the corrosion inhibitor is composed of 1,2,4-triazole and polyvinyl pyrrolidone in a mass ratio of 2.5:1.
[0062] Furthermore, the surfactant is composed of dodecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether in a mass ratio of 1:1.1.
[0063] Furthermore, the pH regulator is potassium dihydrogen phosphate-potassium hydrogen phosphate buffer.
[0064] The method for preparing the efficient and environmentally friendly polishing liquid described in this embodiment includes the following steps: mixing nano metal abrasives, silicon oxide abrasives and deionized water into a suspension and ultrasonically dispersing the suspension, then adding an oxidant, a corrosion inhibitor, a complexing agent and a surfactant thereto and stirring them evenly, and then adding a pH adjuster to adjust the pH of the solution to 8.0.
[0065] Example 4
[0066] The present embodiment provides an efficient and environmentally friendly chemical polishing liquid, comprising the following raw materials in weight percentage: 8% nano-metal abrasive, 3% silicon oxide abrasive, 8% oxidant, 4% complexing agent, 0.4% corrosion inhibitor, 0.25% surfactant, and the rest is deionized water; it also includes a pH regulator, and the pH of the chemical polishing liquid is adjusted to 8.5 by the pH regulator.
[0067] Furthermore, the nano metal abrasive is composed of Sm-doped nano cerium oxide and nano aluminum oxide in a mass ratio of 1:0.7.
[0068] Furthermore, the preparation method of the Sm-doped nano-cerium oxide includes the following steps: taking 1g of cerium nitrate and fully dissolving it in deionized water to obtain a cerium nitrate solution, then adding 1ml of acetic acid and 30ml of ethylene glycol solution to the cerium nitrate solution in sequence and stirring it evenly, then dropping the samarium nitrate solution therein, and then transferring it to a reactor, reacting at 180°C for 3h, cooling naturally after the reaction, removing the supernatant by centrifugation, repeatedly washing with water and ethanol, drying in an oven at 60°C overnight, and calcining at 500°C for 4h to obtain the Sm-doped nano-cerium oxide.
[0069] Furthermore, the concentration of the cerium nitrate solution is 1.2 g / mL, and the concentration of the samarium nitrate solution is 0.5 g / mL. The average particle size of the Sm-doped nano-cerium oxide obtained by the above preparation steps is 130 nm, and the atomic percentage of Sm doped in the cerium oxide is 2%.
[0070] Furthermore, the nano-alumina is a nano-alumina having a silicon oxide coating layer on the surface, and its preparation method comprises the following steps: taking 1g of nano-alumina into a reactor, adding 80mL of ethanol and 20mL of deionized water in sequence, ultrasonically mixing, then adding 5g of hexadecyltrimethylammonium bromide and sodium hydroxide thereto and mixing evenly, then adding TEOS dropwise, stirring and reacting at room temperature for 12h, and after completion, centrifuging, washing and drying to obtain the nano-alumina having a silicon oxide coating layer on the surface.
[0071] Furthermore, the particle size of the nano-aluminum oxide is 10 nm; and the thickness of the silicon oxide coating layer is 12 nm.
[0072] Furthermore, the particle size of the silicon oxide abrasive is 40nm. The preparation method of the silicon oxide abrasive comprises the following steps: adding an ammonia-ammonium chloride buffer solution to a container containing deionized water, and stirring thoroughly to obtain a buffer solution with a pH of 10.5; then adding a small amount of ethyl orthosilicate (the mass ratio of deionized water to ethyl orthosilicate is 1.2:1) to the buffer solution, heating to 75°C while stirring, reacting for 12h to obtain silica sol, and then subjecting the silica sol to rotary evaporation at 50°C, and vacuum drying to obtain the silicon oxide abrasive.
[0073] Furthermore, the oxidant is hydrogen peroxide.
[0074] Furthermore, the complexing agent is composed of glycine and potassium hydrogen phthalate in a mass ratio of 2:1.
[0075] Furthermore, the corrosion inhibitor is composed of 1,2,4-triazole and polyvinyl pyrrolidone in a mass ratio of 3:1.
[0076] Furthermore, the surfactant is composed of dodecyltrimethylammonium bromide and fatty alcohol polyoxyethylene ether in a mass ratio of 1:1.2.
[0077] Furthermore, the pH adjuster is polyhydroxy diamine.
[0078] The method for preparing the efficient and environmentally friendly polishing liquid described in this embodiment includes the following steps: mixing nano metal abrasives, silicon oxide abrasives and deionized water into a suspension and performing ultrasonic dispersion, then adding an oxidant, a corrosion inhibitor, a complexing agent and a surfactant thereto and stirring evenly, and then adding a pH adjuster to adjust the pH of the solution to 8.5.
[0079] Comparative Example 1
[0080] The difference between this comparative example and Example 1 is that commercially available silicon oxide (Hangzhou Jiupeng New Materials Co., Ltd., with a particle size of 30 nm) is used to replace the silicon oxide abrasive in Example 2.
[0081] Comparative Example 2
[0082] The difference between this comparative example and Example 3 is that commercially available cerium oxide (HN-Ce03, Hangzhou Hengna New Materials Co., Ltd.) and commercially available aluminum oxide (ALuna-2032, Hubei Huifu Nanomaterials Co., Ltd.) are used to replace the nano-cerium oxide and nano-aluminum oxide in Example 2, and the mass ratio remains unchanged.
[0083] Comparative Example 3
[0084] The difference between this comparative example and Example 3 is that undoped nano-cerium oxide is used to replace the nano-metal abrasive in Example 3.
[0085] Comparative Example 4
[0086] The difference between this comparative example and Example 3 is that nano-alumina (ALuna-2032, Hubei Huifu Nano Materials Co., Ltd.) is used to replace the nano-metal abrasive in Example 3.
[0087] Comparative Example 5
[0088] The difference between this comparative example and Example 3 is that the nano-metal abrasive in the example is replaced by an equal amount of silicon oxide abrasive in this comparative example.
[0089] In order to verify the polishing effect of the chemical polishing liquid of the present invention, the polishing liquid prepared in the above Examples 1-4 and Comparative Examples 1-5 was used to finely polish a single crystal silicon wafer. The polishing process parameters are: the grinding and polishing disc speed is 80 rpm, the carrier disc speed is 60 rpm, the polishing liquid flow rate is 12 ml / min, the polishing pressure is 36 kPa, the polishing time is 1 h, and the polishing pad is a frosted leather polishing pad. The test results are shown in the following table:
[0090]
[0091] From the above results, it can be seen that compared with comparative examples 1-5, the chemical polishing liquid prepared in Examples 1-4 of the present invention has a good polishing effect on the surface processing of single crystal silicon wafers, has a high material removal efficiency, and the surface roughness of the polished silicon wafer is low, and is used for precision processing of single crystal silicon wafers. At the same time, the raw materials used in this type of chemical polishing liquid are environmentally friendly and have no harm to the environment and human body.
[0092] On the other hand, the chemical polishing liquids prepared in Examples 1-4 were left at room temperature for 7 days. The results showed that the four groups of polishing liquids still had a large amount of suspended abrasives after 7 days, and the sedimentation was less, which shows that the abrasives in the polishing liquids prepared by the present invention have good dispersibility and high stability. The chemical polishing liquids prepared in Comparative Examples 1-5 all showed different degrees of sedimentation, and the sedimentation degree from light to heavy was Comparative Example 1, Comparative Example 3, Comparative Example 2, Comparative Example 5 and Comparative Example 4.
[0093] The above specific embodiments are further explanations of the technical solutions and beneficial effects of the present invention, and are not limitations of the implementation methods. For those skilled in the art, any obvious replacements that do not depart from the concept of the present invention are within the protection scope of the present invention.
Claims
1. A highly efficient and environmentally friendly chemical polishing solution, characterized in that A chemical polishing liquid comprises the following raw materials in weight percentage: 5%-8% nano-metal abrasive, 2%-4% silicon oxide abrasive, 2%-10% oxidant, 1%-5% complexing agent, 0.05%-0.5% corrosion inhibitor, 0.01%-0.3% surfactant, and the rest is deionized water; and also comprises a pH regulator, and the pH value of the chemical polishing liquid is adjusted to 7.5-8.5 by the pH regulator.
2. The highly efficient and environmentally friendly chemical polishing liquid according to claim 1, characterized in that: The nano metal abrasive comprises at least one of nano cerium oxide, nano aluminum oxide and nano zinc oxide.
3. The highly efficient and environmentally friendly chemical polishing liquid according to claim 2, characterized in that: The nano metal abrasive is composed of nano cerium oxide and nano aluminum oxide in a mass ratio of 1:0.5-0.
7.
4. The efficient and environmentally friendly chemical polishing liquid according to claim 1, characterized in that: The particle size of the silicon oxide abrasive is 30-60 nm.
5. The efficient and environmentally friendly chemical polishing liquid according to claim 1, characterized in that: The oxidant is any one of hydrogen peroxide, NaClO, and K2S2O8.
6. The efficient and environmentally friendly chemical polishing liquid according to claim 1, characterized in that: The complexing agent is at least one of glycine, potassium hydrogen phthalate and sorbitol.
7. The efficient and environmentally friendly chemical polishing liquid according to claim 1, characterized in that: The corrosion inhibitor is at least one of 1,2,4-triazole, polyvinyl pyrrolidone, disodium hydrogen phosphate and sodium benzoate.
8. The efficient and environmentally friendly chemical polishing liquid according to claim 1, characterized in that: The surfactant is at least one of octylphenol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, hexadecyltrimethylammonium bromide and sodium dodecylbenzene sulfonate.
9. The efficient and environmentally friendly chemical polishing liquid according to claim 1, characterized in that: The pH regulator is at least one of dihydrogen phosphate-hydrogen phosphate buffer, aminopropanol, polyamine organic base, oxalic acid, and L-malic acid.
10. The method for preparing a highly efficient and environmentally friendly chemical polishing solution according to any one of claims 1 to 9, characterized in that: The method comprises the following steps: mixing nano metal abrasive, silicon oxide abrasive and deionized water into a suspension for ultrasonic dispersion, then adding an oxidant, a corrosion inhibitor, a complexing agent and a surfactant thereto and stirring evenly, and then adding a pH regulator to adjust the pH of the solution to 7.5-8.5.
Citation Information
Patent Citations
Polishing liquid for polishing monocrystalline silicon piece chemical machine
CN101671528A
Polishing liquid for reducing microscratch of surfaces of silicon wafers and preparation and use method thereof
CN102061131A
Preparation method for super-precise polished core-shell structure composite slurry
CN103509470A
Anti-cleavage polishing solution for gallium oxide wafer and preparation method of anti-cleavage polishing solution
CN105153943A
Preparation method and application of lanthanide series metal-doping cerium dioxide nanometer abrasive particles
CN108410424A
Cited By
Environment-friendly grinding and polishing solution based on biodegradable material and preparation method of environment-friendly grinding and polishing solution
CN120758178A
Environment-friendly grinding and polishing liquid based on biodegradable material and preparation method thereof
CN120758178B
Strong-corrosivity rough polishing liquid suitable for rough polishing of silicon wafer and preparation method of strong-corrosivity rough polishing liquid
CN120758179A